Return to oakpine eaudiobook - Carlson, Ron (Recorded Books Inc., 2013)
Ron Carlson is a widely respected author whose accolades include a National Endowment for the Arts fellowship and a Ploughshares Cohen Prize. Return to Oakpine spins a story of growing up and growing old as four high school friends and former bandmates reconnect 30 years after graduating. When they learn that one of them is dying, it feels like getting the band back together might be the most important thing they can do.